Digital Feminism and Patriarchal Resistance: Gita Savitri’s Critique of Patriarchy on YouTube - Mufidah, Eni; Zaini Dahlan (Faculty of Ushuluddin and Philosophy, 2023)
Patriarchy is a social structure deeply rooted in Indonesian culture, influencing various aspects of life, including education, economy, and politics. This study aims to analyze how Gita Savitri, through her YouTube channel, constructs a critical discourse against patriarchal culture, using Qāsim Amīn's feminist paradigm as a framework for analysis. This research uses qualitative methods through a literature review and critical discourse analysis of the video content produced by Gita. The results show that Gita utilizes digital media as an alternative space to voice gender equality and criticize the normalization of injustice against women. The rhetorical strategies used include raising awareness, deconstructing stereotypes, and affirming women’s autonomy. This study finds that although digital spaces often reproduce patriarchal power relations, social media can also be an effective arena for resistance, particularly among urban Muslim youth. Thus, this research expands the study of digital feminism in Indonesia and highlights the importance of utilizing new platforms to achieve more inclusive and egalitarian social and religious transformation.